2004
DOI: 10.1097/01.qai.0000141252.16099.af
|View full text |Cite
|
Sign up to set email alerts
|

Migration and AIDS in Mexico

Abstract: Studies to evaluate the impact of international migration on distribution of infected persons will be indispensable to establish priorities in prevention and attention among migrants. More information is needed on bi-national health projects to understand the impact they may have in prevention, while continuity of the prevention initiatives must be guaranteed. Attention to migrants in bi-national contexts requires information exchange agreements on migrants living with the HIV/AIDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
1
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(28 citation statements)
references
References 6 publications
(6 reference statements)
0
25
1
2
Order By: Relevance
“…Studies in India revealed that 30% of migrant workers have higher rates of risky sexual behaviors such as non-marital sexual intercourse at the place of destination [14]. Other studies in South Africa (31.4%), North Carolina (46%), and California (30%) indicated that migrant workers living apart from their wives are likely to engage in higher rates of multiple and commercial sex [13,15,16]. Studies in India (25%), South Africa (33%), and Croatia (44.7%) revealed that condom use is less practiced among seasonal migrant workers having sexual contact with any casual or commercial sexual partners [17-19].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in India revealed that 30% of migrant workers have higher rates of risky sexual behaviors such as non-marital sexual intercourse at the place of destination [14]. Other studies in South Africa (31.4%), North Carolina (46%), and California (30%) indicated that migrant workers living apart from their wives are likely to engage in higher rates of multiple and commercial sex [13,15,16]. Studies in India (25%), South Africa (33%), and Croatia (44.7%) revealed that condom use is less practiced among seasonal migrant workers having sexual contact with any casual or commercial sexual partners [17-19].…”
Section: Introductionmentioning
confidence: 99%
“…A large proportion of men who attended the Family PACT clinics generally were seeking treatment of an STI before returning home to their families left behind in Mexico. This has important implications for their wives or partners in California and Mexico, who, because of traditional feminine roles in Mexico, and the associated low degree of power, may have limited ability to negotiate sexual practices with their partners, such as condom use, or to discuss men's previous sexual histories while in the USA (Magis-Rodriguez et al 2004). Numerous other studies have confirmed that female partners of Mexican men who travel to the USA may be unknowingly at high risk for STIs, including HIV/AIDS (Hirsch et al 2002;Brammeier et al 2008;Caballero-Hoyos et al 2008).…”
Section: Discussionmentioning
confidence: 97%
“…Studies have found that they are more likely to engage in risk-related sexual practices in the USA, such as a higher number of partners, sex with sex workers and increased substance abuse (Organista et al 1997;Viadro and Earp 2000;Magis-Rodriguez et al 2004;O'Brien, Hunt, and Hart 2005;Brammeier et al 2008). Migration has been found to be a risk factor for HIV and other sexually-transmitted infections (STIs) in several studies among Mexican immigrants (Magis-Rodriguez et al 2004;Organista, Carrillo, and Ayala 2004;Erlich, Organista, and Oman 2007;Rhodes et al 2008). Latinos in the USA are disproportionately affected by sexually transmitted infections and STI rates continue to rise among this population (Center for Disease Control 2007).…”
Section: Introductionmentioning
confidence: 98%
“…For example, prioritised health strategies in Mexico focus on Pre-departure conditions, such as limited access to condoms and testing and social norms regarding sexuality, by using mobile health units, campaigns to incorporate HIV testing into routine primary care visits, and mass media campaigns addressing homophobia, gender inequality, and stigma related to HIV (Izazola Licea et al 2010; Magis-Rodriguez et al 2004; Strathdee and Magis-Rodriguez 2008). …”
Section: Discussionmentioning
confidence: 99%